Preferencje w zakresie wykorzystania metod zarządzania z perspektywy praktyki - Błaszczyk, Wanda (Preferences regarding the use of management methods in view of practice, 2005)
The article presents the results of analysis of the use of management methods in the practice of selected contemporary organizations. Attention was paid to the premises of undertaken interventions improving the organization's functioning; furthermore, applied management methods were characterized in terms of their type and scope, and areas of implementing individual management methods into practice were indicated.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 33-40